Functionalization of cotton by reduced graphene oxide for improved electrical conductivity. Issue 6 (March 2019) - He, Shan; Xin, Binjie; Chen, Zhuoming; Liu, Yan
In this study, electrically conductive cotton fabric is prepared by a "dip and dry" method with graphene oxide (GO) nanosheets following by a reducing process with hydrazine hydrate. For a more practical application, an interfacial modification on the cotton fabric is conducted by using a functional silane coupling agent (KH-560) to enhance the binding force of GO and the fabric, which can increase the durability properties of the conductive fabric. The bonding mechanism among the cotton, KH-560 and GO is analyzed. The influences of the mass fraction of GO and the dipping cycle in GO dispersed solution on the properties of the conductive cotton fabric are investigated. The experimental results show that the optimal GO mass fraction for a good electrical conductivity of the resultant fabric (namely the reduced GO/KH-560/cotton) is 0.8%. In addition, the conductivity of the fabric is highest after five dipping cycles when prepared with a certain mass fraction of GO. Moreover, the durability properties of reduced GO/KH-560/cotton can be significantly improved when treated with KH-560. The prepared conductive fabric with a high flexibility, durability and excellent conductivity has a promising application for the preparation of wearable electronics, outdoor products, etc.